Pemetaan Intensitas Radiasi Medan Elektromagnetik Pada Kawasan Base Transceiver Station (BTS) Jl. Kenangan 05 dan Dampak Kesehatan di Masyarakat. - Siti Khadijah; Adrianus Inu Natalisanto; Pratiwi Sri Wardani (Jurnal Inotera, 2024)
Electromagnetic waves are a type of wave phenomenon. Electromagnetic waves are transverse waves that arise due to changes in electric fields and magnetic fields that oscillate with each other. Electromagnetic waves can be generated, one of the ways, from BTS towers so that they can produce intense electromagnetic field radiation. Health problems resulting from exposure to electromagnetic wave radiation cannot be felt directly. However, the longer you are exposed to electromagnetic wave radiation, the more dangerous it will be to your body's health. The aim of this research is to carry out mapping from measuring the intensity of electromagnetic field radiation in the BTS area and to determine the health impact of large electromagnetic field radiation on the surrounding community. Data processing in this research was carried out using quantitative techniques and qualitative techniques, namely by measuring the intensity of the electric field and magnetic field of electromagnetic waves and evaluating the results of the intensity of electromagnetic field radiation as well as conducting interviews as a public health survey. The data obtained in this research was processed using ArcGis and Surfer software for mapping results. Based on the evaluation and mapping results, it shows that the intensity of electromagnetic field radiation is still below the threshold value according to the 2020 ICNIRP standards. Based on the results of this research, there are no significant health effects occurring in the surrounding community.